Easier, simpler, faster : systems strategy for lean IT - Cunningham, Jean E.; Jones, Duane, 1958- (Productivity Press, 2020)
To enhance and sustain its Lean journey, a company must implement information systems that fully support and enhance the Lean initiative. In Easier, Simpler, Faster: Systems Strategy for Lean IT, Jean Cunningham and Duane Jones introduce the case study of an actual Lean implementation involving the IT system of a mid-size manufacturer, highlighting the IT challenges that the manufacturer faced during the Lean transformation. Winner of aShingo Prize, thisbook will provide you with a broader vision as well as a path to what a Lean system environment will look like for your company.